Expanding Technologized Theatre to Perform Intermedial Dramaturgy - Yudiaryani; Hirwan Kuardhani; Pius Rino Pungkiawan (Institut Seni Indonesia Padangpanjang, 2024)
This article attends to how the utilization of technological devices in twenty-first-century theatre performances can influence audiences' perception of the relationship between humans and technology. Representing artists' work in the fields of new media dramaturgy, intermedial performance strengthens the role of the human body in performance by organizing the embodiment as a technologized theatre strategy. This means that through theatrical technologization, the theatre expands into intermedial performance. This research applies Marco de Marinis' semiotic theory and Chiel Kattenbelt's intermedial theory as the formal objects. A contemporary performance, Jack the Robot performance, becomes the material object. The research uses a hermeneutic qualitative method. The data analysis technique is to reduce and classify data to discover concepts and theories between data in practice. The findings show that dramaturgy is no longer treated only as science, technology, and art, but its benefits are extended to society. Human resources' creativeness and expanded capacity return the body of art organically into interdisciplinary, intercultural, and educational embodiment. Dramaturgy, expanded with theatrical technologization, in its exploration extends to the intersection between embodiment, mise-en-scène, intermedial space, and its impact on the audiences' perception.